Pengaruh Aset Pajak Tangguhan, Profitabilitas Dan Perencanaan Pajak Terhadap Manajemen Laba - Mohamad Husni Mohamad Husni; Riyanthi Idayu (Universitas Serang Raya, 2022)
This study aims to determine whetever there is the effect of deferred tax assets, profitability and tax planning on profit management in companies subsectors food and beverage companies listed on the Indonesia Stock Exchange Period 2016-2020 partially or simultaneously. In this study, the samples used were food and beverage subsector companies as many as 7 companies with financial report data for the period 2016-2020 through purposive samplingtechniques. Variabel this research is processed using instrument measuring instrument SPSS version 25.The results of the study hypothesized that deferred tax assets with the acquisition of t valuecalculate < ttable (-2,994 < -2.03693) and sig value (α) of (0.005 < 0.05), profitability t calculate < ttable (1,825 < 2.05 03693), sig (α) value of (0.078 > 0.05) tax planning t count < ttable (0.809 < 2.03693), value sig (α) of (0.425 > 0.05). Obtained value Fcount > Ftable (4,177 > 2.91) and value sig (α) of (0.014 < 0.05).